Socioeconomic differences in incidence and relative survival after a first acute myocardial infarction in the Basque Country, Spain Diferencias socioeconómicas en la incidencia y supervivencia relativa del infarto agudo de miocardio en el País Vasco - Mónica Machón; Elena Aldasoro; Pablo Martínez-Camblor; Montse Calvo; Mikel Basterretxea; Covadonga Audicana; Eva Alonso; M.ª Cres Tobalina; Nerea Larrañaga (Elsevier, 2012)
Objective: To estimate the incidence and 28-day and 5-year survival rates after a first acute myocardial infarction (AMI) in relation to socioeconomic status in the Basque Country (Spain) between 1999 and 2000. Methods: Data from a population-based registry of AMI were used. The study included 3,619 patients to calculate age-standardized incidence by the direct method and 2,003 patients (out-of-hospital deaths were excluded) to calculate observed and relative survival using the Kaplan-Meier and Hakulinen methods, respectively. Socioeconomic status was quantified using a deprivation index ecologically assigned to each patient according to the census tract of residence at diagnosis of AMI and was categorized into quintiles. Results: Among men, the risk of AMI was higher in the lowest socioeconomic group than in the highest socioeconomic group (RR=1.17; 95%CI: 1.02-1.34). In men, a higher risk of death was observed in the middle (Q3; HR=1.60; 95%CI: 1.02-2.51) and low (Q5; HR=1.65; 95%CI: 1.02-2.69) quintiles compared with the least deprived group for age-adjusted survival during the acute phase. In the fully adjusted model, this effect was attenuated and no significant differences were observed in long-term survival. Among women, no significant differences were observed either in incidence or in short- and long-term survival. Conclusions: Socioeconomic inequalities were only observed in men in incidence and in survival during the acute phase after an AMI. Objetivo: Estimar la incidencia y la supervivencia a 28 días y 5 años tras un primer infarto agudo de miocardio (IAM) según la posición socioeconómica en el País Vasco entre 1999 y 2000. Métodos: Utilizando datos de un registro poblacional de IAM se incluyeron 3.619 pacientes para estimar la incidencia ajustada por edad por el método directo, y 2003 (excluidas las muertes extrahopitalarias) para la supervivencia observada y relativa con el método de Kaplan-Meier y el de Hakulinen, respectivamente. El nivel socioeconómico se definió por un índice de privación ecológicamente asignado a cada paciente según la sección censal de residencia al diagnóstico del IAM, y se categorizó en quintiles. Resultados: Los hombres del nivel socioeconómico más bajo tuvieron un mayor riesgo de IAM que los del más alto (RR=1,17; IC95%: 1,02-1,34). En la supervivencia en la fase aguda ajustada por edad, los hombres de los quintiles medio (Q3; HR=1,60; IC95%: 1,02-2,51) y bajo (Q5; HR=1,65; IC95%: 1,02-2,69) presentaron un mayor riesgo de muerte en comparación con el grupo más favorecido. Este efecto se vio atenuado en los modelos completamente ajustados, y no hubo diferencias significativas en la supervivencia a largo plazo. En la mujeres no se hallaron diferencias significativas en la incidencia ni en la supervivencia a corto y largo plazo. Conclusiones: Sólo se han observado desigualdades socioeconómicas en los hombres en la incidencia y la supervivencia durante la fase aguda.